2018
DOI: 10.1038/s41598-018-26846-y
|View full text |Cite
|
Sign up to set email alerts
|

Linear Elastic Fracture Mechanics Characterization of an Anisotropic Shale

Abstract: The existence of bedding planes in natural shale formations makes the fracture characterization remarkably complicated. To achieve a further understanding of the anisotropic crack extension behaviors of shale using a linear elastic fracture mechanics approach, four groups of three-point bending tests on Longmaxi shale from southeast Chongqing were conducted in this study with different bedding plane inclination angles. The fracture propagation paths were observed using a scanning electron microscope. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…More recently, a number of groups have addressed fracture toughness measurement in shales, with studies by Lee et al (), Chandler et al (, ), Chen et al (), Kabir et al (), Luo et al (), and Forbes Inskip et al (). Lee et al () used semicircular bend specimens to measure fracture toughness in the Divider and Arrester orientations in the Marcellus shale, as well as at an angle of 30° to the Arrester orientation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, a number of groups have addressed fracture toughness measurement in shales, with studies by Lee et al (), Chandler et al (, ), Chen et al (), Kabir et al (), Luo et al (), and Forbes Inskip et al (). Lee et al () used semicircular bend specimens to measure fracture toughness in the Divider and Arrester orientations in the Marcellus shale, as well as at an angle of 30° to the Arrester orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Even at the slowest scratch speeds that they test, they found fracture toughnesses in the region of 2 Mpa.m 12. Luo et al () and Forbes Inskip et al () each used bend specimens to investigate the variation of K Ic in the Arrester, Short‐Transverse, and Divider orientations, as well as at angles between the Arrester and Short‐Transverse orientations. Luo et al () investigated the Chongqing shale, and found K Ic to vary in the ≃0.9–1.6 Mpa.m 12 range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydraulic fracturing in shale is important for the sealing capacity of shale layers during natural (Foschi et al, ; Petrie et al, ) and artificial (Elkhoury et al, ) fluid‐expulsion events. The mechanical anisotropy of shale is evident from its fissility in hand samples, from abundant examples of layer‐parallel natural fractures hosted in shales worldwide (Cobbold et al, ; Gale et al, ; Hooker et al, ) and from laboratory experiments indicating that shale has a lower surface energy along bedding planes than across them (Chandler et al, ; Luo et al, ). This anisotropy could therefore guide fracture propagation into a layer‐parallel orientation, improving the effective sealing capacity of shales.…”
Section: Introductionmentioning
confidence: 99%